Eco-evolutionary dynamics of host-microbiome interactions in a natural population of closely related mouse subspecies and their hybrids - Ferreira, Susana C M; Jarquín-Díaz, Víctor Hugo; Planillo, Aimara; Ďureje, Ľudovít; Martincová, Iva; Kramer-Schadt, Stephanie; Forslund-Startceva, Sofia K; Heitlinger, Emanuel (Proceedings. Biological sciences, 2024)
Closely related host species share similar symbionts, but the effects of host genetic admixture and environmental conditions on these communities remain largely unknown. We investigated the influence of host genetic admixture and environmental factors on the intestinal prokaryotic and eukaryotic communities (fungi, parasites) of two house mouse subspecies (Mus musculus domesticus and M. m. musculus) and their hybrids in two settings: (i) wild-caught mice from the European hybrid zone and (ii) wild-derived inbred mice in a controlled laboratory environment before and during a community perturbation (infection). In wild-caught mice, environmental factors strongly predicted the overall microbiome composition. Subspecies' genetic distance significantly influenced the overall microbiome composition, and each component (bacteria, parasites and fungi). While hybridization had a weak effect, it significantly impacted fungal composition. We observed similar patterns in wild-derived mice, where genetic distances and hybridization influenced microbiome composition, with fungi being more stable to infection-induced perturbations than other microbiome components. Subspecies' genetic distance has a stronger and consistent effect across microbiome components than differences in expected heterozygosity among hybrids, suggesting that host divergence and host filtering play a key role in microbiome divergence, influenced by environmental factors. Our findings offer new insights into the eco-evolutionary processes shaping host-microbiome interactions.
Keywords: biologická evoluce; střevní mikroflóra; Host Microbial Interactions; spatial environment; interakce mikroorganismu a hostitele; Mice; Biological Evolution; Gastrointestinal Microbiome; Microbiota; mikrobiota; hybridization; host–microbiome interactions; microbiome; zvířata; Hybridization, Genetic; myši; hybridizace genetická; species barriers; Animals